1983
DOI: 10.1111/j.1432-1033.1983.tb07623.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of enzymes of fatty acid and ketone body metabolism in periportal and perivenous rat‐liver tissue

Abstract: The zonal distribution of cytosolic acetyl-CoA carboxylase, mitochondria1 3-hydroxyacyl-CoA dehydrogenase and 3-hydroxybutyrate dehydrogenase was studied in microdissected liver tissue.1. In fed male and female rats the activity of the lipogenic enzyme acetyl-CoA carboxylase was 1.6-times higher in the perivenous than in the periportal zone of the liver acinus.2.3-Hydroxybutyrate dehydrogenase, which is involved in the formation of the ketone body, 3-hydroxybutyrate, exhibited a similar distribution pattern wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 25 publications
2
31
1
Order By: Relevance
“…Hepatic lipogenic enzymes appear to have a more perivenous distribution (32,33), whereas the rate-limiting step in bile acid synthesis, cholesterol 7␣-hydroxylase, is found mainly in periportal hepatocytes (34). Expression of hBACS was also found to have a more periportal distribution.…”
Section: Discussionmentioning
confidence: 92%
“…Hepatic lipogenic enzymes appear to have a more perivenous distribution (32,33), whereas the rate-limiting step in bile acid synthesis, cholesterol 7␣-hydroxylase, is found mainly in periportal hepatocytes (34). Expression of hBACS was also found to have a more periportal distribution.…”
Section: Discussionmentioning
confidence: 92%
“…Because of reported hepatocyte heterogeneity in some of the elements related to hepatic lipid metabolism including LRP, 40 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase, [41][42][43] cholesterol 7␣-hydroxylase, [44][45][46] Golgi VLDL, 47 and fatty acid metabolism, 48 the present study was undertaken to establish whether ApoE expression is heterogeneous in the liver at the cellular level and whether this heterogeneity shows a distinct lobular pattern. Because of known sexual dimorphism in lipid metabolism, we also determined whether there were male-female differences in liver ApoE mRNA expression level and lobular distribution pattern.…”
mentioning
confidence: 99%
“…Applying microanalytical techniques on microbiopsies from the PP and PV zones of the liver microcirculation, Katz et al [3] observed an approximately 60% higher ACC activity and a 100% higher activity of ATP citrate lyase [4] in the PV zone of the rat liver (table 1). The zonation in the fasted state was somewhat lower than in the fed and refed state.…”
Section: Review Of the Apparently Contradictory Resultsmentioning
confidence: 99%
“…Most results obtained by the microanaly sis technique using microdissected samples are expressed per milligram of dry weight, as is the case in the studies by Katz et al [3,4,6], while the studies on isolated hepatocytes are usually expressed per milligram of total protein [9,10,16] or in some studies per milligram of DNA [7,16]. Contrary to this, the results of Evans et al [11,12] on the zon ation of ACC, applying digitonin-pulse per fusion [14], are expressed per milligram of cytosolic protein or as the true specific activ ity, since the assay was performed also with the isolated ACC protein.…”
Section: Expression Of Results: Choice Of Reference Substancementioning
confidence: 99%
See 1 more Smart Citation